Synthesis and Biological Activity of Some 3,4-Dihydro-4-(4-substituted aryl)-6-(naptho[2,1-b]furan-2-yl pyrimidine-2(1H)-one Derivatives - Sanjeevan S. Gaikwad; Venkat S. Suryawanshi; Kishan S. Lohar; Dhanaji V. Jadhav; Narayan D. Shinde (E-Journal of Chemistry)
A series of new oxopyrimidine were prepared by cyclocondensation route with various substituted chalcones in presence of alcoholic solution of potassium hydroxide at reflux temperature. The synthesized oxopyrimidine derivatives were characterized by means of their IR, 1H NMR, mass spectral data and elemental analysis. The synthesized oxopyrimidines derivatives were evaluated for antibacterial and antifungal activities, some of them were found to possess significant activity.